Preliminary study on the prevalence of giardia in ruminants in ninevah province - M. SH. Rhaymah; B. A. Mohammed (Iraqi Journal of Veterinary Sciences, 2006)
The study revealed presence of giardia cyst in the feces of animals which was examined at 7%, 4.5% and 5.45% in the direct method for sheep, goats and cattle respectively, while 15.5%, 16.5% and 21.81% in concentrated method respectively at the same animals. No significant differences recorded in rate of infection between different species of animals, although higher percentage of cyst was eliminate in cattle feces. There was no significant effect of age and type of breeding on rate of infection. However the animals in late stage of pregnancy and early stages of milking eliminated higher percentage of cyst in their feces, especially in goats. Diagnosis of gastrointestinal nematode eggs with giardia was found to be 7.5%, 4.5 and 0 % in sheep, goats and cattle, respectively and with Eimeria; 3.5%, 11% and 5.45, in same animals, respectively. The most obvious clinical signs found were pasty feces mixed with mucous, emaciation and easily detached wool and hair.